Transformation of Local and National Themes in Muhsen Yousef's Stories - Mohammad Marrosheh (دراسات فی اللغه العربیه و آدابها)
This study deals with Muhsen Yousef's creative experience, starting with his first collection, Faces of Late Night and ending with his last collection, Mrs Jamila. However, the study is not a survey of the writer's creative experience it rather traces the development of creative storytelling in this author so as to discover the transformations of the local and national themes in his works. The study also follows the changes his creative experience has undergone as well as the writer's intellectual orientation. It, also, discusses the technical devices employed by the writer such as subdivisions, headings, internal monologues and stream of consciousness. However, it should be noted that the writer does not straitiacket his work by using modern terms rather, he tries to preserve his own individual narrative voice, using a lively narrative style.